2020
DOI: 10.1111/jpn.13461
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyphenols can directly affect ovarian cell functions and modify toluene effects

Abstract: The influence of toluene alone and in combination with plant polyphenols apigenin, daidzein or rutin on viability, proliferation (proliferating cell nuclear antigen accumulation), apoptosis (Bax accumulation) and release of progesterone (P), testosterone (T) and estradiol (E) in cultured porcine ovarian granulosa cells was evaluated. Toluene reduced ovarian cell viability, proliferation and E release; it promoted P release, demonstrating no effect on apoptosis or T output. Apigenin alone failed to affect cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…The comparison of the effects of elderberry extract and rutin showed the similar effects for the extracts and its major component. In experiments of Sirotkin et al [8,89], the addition of rutin was found to increase the viability of cultured porcine ovarian granulosa cells, although this effect was not associated with changes in the accumulation of markers of proliferation (accumulation of PCNA) and cytoplasmic apoptosis (Bax). In vivo experiments, like in vitro ones, demonstrated the stimulatory action of rutin on rat ovarian cell health and ovarian folliculogenesis [90,91].…”
Section: Effect Of Elderberry and Its Constituents On Ovarian Cell Vi...mentioning
confidence: 88%
See 1 more Smart Citation
“…The comparison of the effects of elderberry extract and rutin showed the similar effects for the extracts and its major component. In experiments of Sirotkin et al [8,89], the addition of rutin was found to increase the viability of cultured porcine ovarian granulosa cells, although this effect was not associated with changes in the accumulation of markers of proliferation (accumulation of PCNA) and cytoplasmic apoptosis (Bax). In vivo experiments, like in vitro ones, demonstrated the stimulatory action of rutin on rat ovarian cell health and ovarian folliculogenesis [90,91].…”
Section: Effect Of Elderberry and Its Constituents On Ovarian Cell Vi...mentioning
confidence: 88%
“…Oxidative stress can be prevented by antioxidants [4]. The most natural, accessible and inexpensive sources of antioxidants, which can affect reproductive processes and prevent numerous reproductive disorders, are plants [6,8]. Additionally, because of implications on health, there is a growing interest in the use of plant-based antioxidants in the food industry.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies reporting its effects on ovarian function are still limited. In our previous in vitro studies, we demonstrated that toluene inhibited ovarian cell viability, proliferation and estrogen release [ 38 , 44 ]. In this study, we investigated the in vivo effect of toluene using female Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other phytoestrogens, such as quercetin (QUE) [62][63][64][65][66][67][68], apigenin (APE) [69][70][71][72][73][74], resveratrol (RES) [75][76][77][78][79], myricetin (MYR) [80][81][82][83][84][85], and are found in many berries, leafy greens, and wine. Although their relative binding affinity differences between ERα and ERβ are not as great as in GEN and DAI, these compounds have been investigated due to their widespread presence in plants and extensive human consumption.…”
Section: Phytoestrogens: Plant-derived Chemicalsmentioning
confidence: 99%
“…Although their relative binding affinity differences between ERα and ERβ are not as great as in GEN and DAI, these compounds have been investigated due to their widespread presence in plants and extensive human consumption. More specifically, QUE, APE, and even RES have been noted to exhibit a biphasic effect; at low concentrations, these phytoestrogens display estrogenic activity, whereas, at higher concentrations, they display more protective anti-estrogenic activity [62][63][64][65][66][67][68][69][70][71][72][73]. Like GEN, RES has been extensively studied in many clinical trials.…”
Section: Phytoestrogens: Plant-derived Chemicalsmentioning
confidence: 99%